Análisis de islas de calor por medio de imágenes satelitales y sistemas de información geográficos en el área urbana de la Sabana de Bogotá - Aragón, Juan Antonio; Rodríguez, Esteban D.; Varon , Gustavo A.; Sánchez, Gabriel A. (Geographicalia, 2020)
In this investigation all data related to Land surface temperature (LST) collected from satellite Landsat 8 was compared to temperature data collected from surface stations located in Sabana de Bogotá, to identify urban heat islands. It was developed a crop in the study area of satellite image in order to processing spectrum bands 10, 4 and 5, using a Land surface Temperature algorithm to collect the satellite mapping of the surface temperature. At the same time, this data was analyzed as statistically as spatially considering the distance and elevation of the stations interpolating them with Cokriging’s method and the ArcGIS 10.3® Software, detecting spatially the geometry of the islands in high urbanization zones, getting the Pixel temperature and comparing it to surface station data finding differences between temperature in urban zones commonly with more vegetation and the two methods used for this study.